Late specialization: the key to success in centimeters, grams, or seconds (cgs) sports - Moesch, K.; Eleb, A.-M.; Hauge, M.-L. T.; Wikman, J. M. (Scandinavian Journal of Medicine & Science in Sports, 2011)
A controversial question within elite sports is whether young athletes need to specialize early, as suggested by Ericsson et al., or if it is more beneficial to follow the path of early diversification proposed by Coté et al., which includes sampling different sport experiences during childhood and specializing later on during adolescence. Based on a Danish sample of 148 elite and 95 near-elite athletes from cgs sports (sports measured in centimeters, grams, or seconds), the present study investigates group differences concerning accumulated practice hours during the early stages of the career, involvement in other sports, career development, as well as determining whether or not these variables predict membership in the elite group. The results clearly reveal that elite athletes specialized at a later age and trained less in childhood. However, elite athletes were shown to intensify their training regime during late adolescence more than their near-elite peers. The involvement in other sports neither differs between the groups nor predicts success. It can be concluded that factors related to the organization of practice during the mid-teens seem to be crucial for international success within cgs sports. Future research should adopt a longitudinal design with means of drawing causal inferences.